DOES ORGANIZATION CULTURE ACTS AS A MEDIATOR IN THE LINKAGE BETWEEN BUSINESS SOCIAL RESPONSIBILITY AND ORGANIZATION PERFORMANCE - Yajid, Mohd Shukri Ab; kKhatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The paper investigated the relation between Business Social responsibility and Organization Performance with the mediation role of organization culture in SMEs in Nigeria. Furthermore, this investigation additionally looks at the intercession impact of hierarchical culture on the connection among BSR and execution. The indicators of BSR are trust, commitment and perceived ethics. A theoretical system was created dependent on surviving literary works and the creative model depends on these BSR builds information was gathered through hand conveyance technique by sending polls to 800 SMEs directors. Partial Least Square (PLS) calculation and bootstrap methods were utilized to test the examination’s speculations. The outcomes intimated the positive association between trust, perceived ethics and performance whereas there is negative relation between commitment and performance in Nigerian context. Furthermore, findings of mediation indicate that all the three hypotheses are significant. Therefore, significant positive effects of commitment, trust, and perceived ethics suggest that the variables are important in relation to performance. The outcome of this study provides significant contributions to both managers and researchers for further understanding on organizational culture and BSR effect on performance. As such, organizations should be encouraged to exhibit these social responsibilities for better performance. Improved performance of organizations can advance the social responsibility practices in organizations. Contributions, limitations, implications and necessary suggestions on the new areas of research are recommended and discussed in this research.